Childhood obesity: a relationship between students of a public and private school - Godoy, Isabela Candreva (2016)
Currently obesity has been treated as a worldwide epidemic, and the increasing number of obese children in Brazilian cities. In most cases, obesity is related to calorie-dense food intake and lack of physical activity. The aim of the study was to analyze the incidence of obesity and overweight among 136 children of a private and public school aged between 07-10 years. For quantifying, the data were used anthropometric methods such as BMI and waist circumference. The results showed prevalence of adequate weight between girls and boys in public schools, and boys of the particular network. The private school girls had a higher incidence of obesity. However, the public boys had become more obese than boys of the private network. For the variable waist circumference, the highest index was concentrated in the private school and the lowest average rate was established at public school. From the results, it was possible to give support to the management of schools for the use of certain intervention strategies aimed at reducing the number of obese children, thus improving the quality of life for its students and reducing the risk of cardiovascular problems.